The Knowledge of Malnutrition-Geriatric (KoM-G) 2.0 Questionnaire for Health Care Institutions: Cross-Cultural Adaptation into German, Czech, Dutch and Turkish - Bauer, Silvia; Pospichal, Jan; Huppertz, Viviënne; Blanar, Vit; Saka, Bulent; Eglseer, Doris (Nutrients, 2024)
It is necessary for nursing staff to have adequate knowledge of malnutrition in older people in order to provide high quality care. This study was conducted to update the Knowledge of Malnutrition-Geriatric (KoM-G) questionnaire to fit different settings and to cross-culturally adapt it to the German, Czech, Dutch and Turkish languages. In Part 1 of the study, the KoM-G questionnaire was updated and adapted for use in different settings. Content validation of the KoM-G 2.0 was carried out in a Delphi study with 16 experts. The final KoM-G 2.0 questionnaire consists of 16 items with a Scale Content Validity Index/Average of 94.5%. In Part 2, the English KoM-G 2.0 was cross-culturally adapted into the German, Czech, Dutch and Turkish languages. In the pilot test, between 96.9% (The Netherlands) and 97.8% (Austria) of the nursing staff rated the items as understandable. The KoM-G 2.0 is an up-to-date questionnaire with a highly satisfactory Content Validity Index. It was cross-culturally adapted into the German, Czech, Dutch, and Turkish languages, and the understandability was high. At the moment, the necessary comprehensive psychometric testing of the KoM-G 2.0 is in process. Afterwards it can be used to compare nurses' knowledge between various countries and settings.
Keywords: dospělí; Germany; průzkumy a dotazníky; Female; Psychometrics; Netherlands; psychometrie; překlady; Delphi Technique; srovnání kultur; Adult; ženské pohlaví; Malnutrition; Surveys and Questionnaires; Reproducibility of Results; lidé; Německo; podvýživa; jazyk (prostředek komunikace); Turkey; delfská metoda; Turecko; reprodukovatelnost výsledků; Nizozemsko; Male; Aged; Translations; Czech Republic; Cross-Cultural Comparison; Health Knowledge, Attitudes, Practice; zdraví - znalosti, postoje, praxe; Language; Česká republika; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans